Chemical pesticide markets, health risks and residues - Harris, Jeremy, (Biopesticides series ;, 2000)
A short book designed to provide a review of information on the scale of manufacture, import, export and use of chemical pesticides, examples of direct risks to human welfare in terms of acute poisonings caused by occupational exposure and pesticide residues in food, and examples of problems with the storage of obsolete stocks of pesticides in developing countries. The main emphasis is on acute problems in developing countries, particularly in Latin America, Asia and Africa, but some information is also provided about developed countries. There are four chapters (Chemical pesticide markets, Pesticide exposure and health effects, Pesticide residues and Obsolete pesticide stocks) and an index is included.